Beyond the Reconquista
1 online resource.
Keywords: "Beyond the Reconquista: New Directions in the History of Medieval Iberia (711-1085) offers an exciting series of essays by leading scholars in Hispanic Studies from across North America and Europe. At its heart is the Reconquista, without doubt the most important and enduring theme of Iberian historiography of the Middle Ages. The innovative studies collected herein, which treat a diverse array of subjects via forensic analyses of charters, chronicles and coins, shed new light on crucial aspects of medieval Iberian socio-economic, political and cultural history. The result is a collection of essays which marks a decisive and bold turning of the page in Iberian medieval studies, as the reality and ideal of Reconquest come under hitherto unparalleled scrutiny. Contributors are Graham Barrett, Jeffrey Bowman, Alberto Canto, Nicola Clarke, Wendy Davies, Julio Escalona Monge, Jonathan Jarrett, Eduardo Manzano Moreno, Iñaki Martín Viso and Lucy K. Pick".